Cuidado de enfermería en paciente adulto mayor hipertenso con accidente cerebro vascular a causa del covid-19. - Pérez Ramírez, Alex German (2021)
The present clinical case is a contribution in the field of health through theoretical and practical knowledge, to act efficiently in the necessary care, identifying problems and needs of the patient, for which the descriptive method was used through data collection Objective and subjective such as physical examination, complementary, analysis and organization for the identification of problems that interfere with the health of the patient, through the Nursing Care Process. In the following clinical case, we present a 56-year-old male patient who came to the Dr. Gustavo Domínguez Hospital when presenting high blood pressure with suspected cerebrovascular accident due to covid-19. Hypertension continues to be a relevant public health problem worldwide, being the main cause of morbidity and mortality and the risk factor with the highest burden attributable to ischemic cardiovascular disease and stroke, there are various factors that contribute to the appearance of hypertension blood pressure such as age, a high sodium intake, diets high in saturated fat, smoking, physical inactivity, the presence of chronic diseases such as obesity, dyslipidemia and diabetes. Having a high relationship with stroke, which is the third cause of death and the first cause of disability.